Loss of Hyperconjugative Effects Drives Hydride Transfer during Dihydrofolate Reductase Catalysis - Angelastro, Antonio (ACS Catal, 2019)
[Image: see text] Hydride transfer is widespread in nature and has an essential role in applied research. However, the mechanisms of how this transformation occurs in living organisms remain a matter of vigorous debate. Here, we examined dihydrofolate reductase (DHFR), an enzyme that catalyzes hydride from C4′ of NADPH to C6 of 7,8-dihydrofolate (H(2)F). Despite many investigations of the mechanism of this reaction, the contribution of polarization of the π-bond of H(2)F in driving hydride transfer remains unclear. H(2)F was stereospecifically labeled with deuterium β to the reacting center, and β-deuterium kinetic isotope effects were measured. Our experimental results combined with analysis derived from QM/MM simulations reveal that hydride transfer is triggered by polarization at the C6 of H(2)F. The σ C(β)–H bonds contribute to the buildup of the cationic character during the chemical transformation, and hyperconjugation influences the formation of the transition state. Our findings provide key insights into the hydride transfer mechanism of the DHFR-catalyzed reaction, which is a target for antiproliferative drugs and a paradigmatic model in mechanistic enzymology.